Born to fly : the first women's air race across America - Sheinkin, Steve (Roaring Brook Press, 2019)
Tells the story of the women who made the 1929 Air Derby--the first women's air race across the United States--possible, including Amelia Earhart, Marvel Crosson, Louise Thaden, and Elinor Smith, each of whom made significant contributions to early flight.